Avaliação de ferramentas de automação de teste: uma análise documental e comparativa - Pessoa, Clinton Hudson Moreira (Brasil, 2020)
In view of the high degree of safety and performance exercised by software, as well as the high level of satisfaction described by its users, many research and companies have come to see not only as a simple trend, but rather as a necessary reality for companies of all sizes. This new way of developing quality software has effective quality and aggregated results satisfactory, however, given the large tangle of tools made available free, it is impracticable to state which is the most efficient among them. For this reason, this work aimed to conduct a survey of the main Open Source test tools that add efficiency in the testing process, newsletter for that purpose a survey informal selection of tools, followed by the application of a questionnaire to test area professionals, identifying 6 more test automation tools uses in the market. With the selected tools, an analysis was performed around the cataloged tools, finalizing their analysis with the Application of some of the standardized quality criteria and made available by NBR ISO / IEC 9126, thus being classified and tabulated in order of compliance or not compliance with the criteria obtained both in terms of documents and the quality of software, ordered with these results to facilitate the choice of automation tools for most appropriate test given the need required in development projects, so it is of course, how to expand research aimed at the automated testing market, contributing with a software test development area and providing support for sources of academic consultations.